Building Research Capacity for Data-Enabled Trials: Embedding Public Perspectives - Lugg-Widger, Fiona; Trubey, Rob; Murray, Macey L; Mafham, Marion; Mackenzie, Isla; Ahmed, Nageen; Cannings-John, Rebecca; Dibigbo, Amaka; Hood, Kerenza; Iheanacho, Daniel; Lloyd, Christopher; Munnery, Kim; et al. (International Journal of Population Data Science, 2025)
The TOP-CAT project, part of the HDR UK-funded Transforming Data for Trials programme, aims to develop training resources for trial teams, public partners, and data custodians. This will strengthen capacity to conduct data-enabled trials and embed public perspectives, to support improved access, use, and transparency of health-systems data in research. A purposively-selected group of 22 public contributors and subject matter experts collaborate with the TOP-CAT team on an ongoing basis to co-develop the training resources. These link to the overarching needs of the programme such as a route-map specific for data-enabled trials. Through structured discussions, available literature and resources, training materials are scripted for ‘talking head’ training videos to be made freely available on HDR UK Futures platform. The resources are iteratively refined through public and expert feedback to ensure relevance to trialists' practical needs and to increase public confidence in data-enabled trials. To date in this five-year programme, four modules have been developed alongside more than 10 standalone ‘short’ videos. Public input shaped training content on key aspects of the training modules: Introductory module, resource hub for public contributors, data governance, and data utility. The resources introduce each topic, provide practical guidance, and include case study examples to support trialists. Public contributors emphasised the need for trial teams to understand the implications of data-enabled methods and prioritise transparency in their work. While developed for trialists, the materials also offer valuable guidance for all researchers working with administrative and health data, particularly governance and data utility considerations. By integrating public perspectives, the training enhances trialists’ confidence in navigating complex data environments while fostering trust and accountability in research. Embedding public perspectives in capacity-building initiatives ensures researchers are equipped to conduct data-enabled trials responsibly. The co-produced resources strengthen governance, transparency, and public trust while offering broader applicability beyond trials. Ongoing collaboration will ensure training remains relevant as the use of health and administrative data in research continues to evolve.